2021
DOI: 10.1186/s41072-021-00094-2
|View full text |Cite
|
Sign up to set email alerts
|

Port choice in Brazil: a qualitative research related to in-depth interviews

Abstract: The choice of port is one of the topics that most interest researchers. Port selection behaviour may vary depending on port user perspectives. Prior studies have attempted to determine user preferences for certain port choice factors, but there are only few studies in developing countries, such as Brazil, where there is a lack of studies on this topic. The objectives of this article are to analyse the port selection factors in Brazil for different port users, to discuss the implications for competitiveness amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…(2020) collected quantitative data from a survey on the competitiveness of container ports perceived by global shipping lines. de Souza et al. (2021) investigated selection factors in Brazil for different port users and revealed that ship calls were the most important, while the concentration of cargo was essential for shipping lines.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…(2020) collected quantitative data from a survey on the competitiveness of container ports perceived by global shipping lines. de Souza et al. (2021) investigated selection factors in Brazil for different port users and revealed that ship calls were the most important, while the concentration of cargo was essential for shipping lines.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, despite the substantial body of literature, sufficient attention has not been given to the effects of COVID-19 on selecting seaports. Seaport selection is an area that requires more attention because it is critical for policymakers, port operators and shipping companies (Bhatti and Hanjra, 2019;de Souza et al, 2021;Hsu et al, 2020;Tiwari et al, 2003). Therefore, it is necessary to find recent changes in seaport selection factors during the COVID-19 pandemic.…”
Section: A Longitudinal Study Of Seaport Selectionmentioning
confidence: 99%
See 3 more Smart Citations